Resultados e significados do programa de aquisição de alimentos (PAA) para os agricultores familiares de Pereira Barreto (SP) - Gonzaga, Douglas de Araujo [UNESP] (2015)
The Programa de Aquisição de Alimentos (Food Acquisition Program), usually called PAA, created by the federal government in 2003, aims to ensure quality food and adequate quantity regularly to the people in food insecurity situation. In addition to benefiting the urban population, the PAA strengthens family farming by purchasing their products. The present research had by objective to characterize the producers, the production and analyze the actions taken in terms of benefits generated, found difficulties, evaluation of the results and perspectives of farmers and entities recipients of food, facing the Program. The methods and research techniques applied were based on the use of questionnaires to farmers located in four (re)settlements surrounding Pereira Barreto (SP), and semi-structured interviews directed to presidents of associations and representatives of benefited entities. Among the effects of the program in the rural (re)settlements surveyed, could be inferred that there was an increase of the area and the number of crops; and generation of an extra income on certain regular basis, which led to investments in the allotment and household goods, resulting in greater motivation of farmers to work in the field. It was found that the greatest obstacles faced by producers are the delay of payment for delivered food and difficulties related to the transport of production. Another important fact pointed out by this research is that participation in the PAA didn't result yet, for the vast majority of producers, on expansion of their marketing channels. Regarding the role of associations in the implementation of the PAA, it was found that the president exerts a crucial role for the formation and performance of itself. In a self- evaluation on the quality of food, farmers mostly classified it as high or good quality products, but some philanthropic entities made restrictions on the food's quality and, as a general rule, critical ...